Bahasa Inggris - Suri Toding Lembang; Kristanto; Daud Rodi Palimbong; Chelin Dion Patimang; Ovalin Paseon; Yenni Pasomba (MaPan : Jurnal Matematika dan Pembelajaran, 2022)
This research implements the carvings of the Toraja Tongkonan house on the transformation geometry material in class XI SMA Negeri 2 Toraja Utara. The purpose of this study was to determine the learning outcomes and student activities in implementing Tongkonan house carvings on the Transformation Geometry material. The research method used is quantitative. Data collection using observation, pre-test, and post-test sheets. An essay test with five question items was used in this study as an instrument. The research sample was a class XI science high school student. Sampling Technique with cluster random sample. This research was conducted at SMA Negeri Toraja in the even semester of 2021. Data analysis techniques are carried out with descriptive statistics in the form of percentage analysis for student activities and student learning outcomes. The results showed that (1) the average score of student activity in learning was 4.05 which can be categorized as active, and (2) student learning outcomes can be categorized as good as evidenced by the average score of student learning outcomes being 76.35.